Impact of palifermin on incidence of oral mucositis and healthcare utilization in children undergoing autologous hematopoietic stem cell transplantation for malignant diseases. (28th November 2013) - Vitale, Kelly M.; Violago, Leah; Cofnas, Paige; Bishop, Jacquelyn; Jin, Zhezhen; Bhatia, Monica; Kung, Andrew L.; George, Diane; Garvin, James; Satwani, Prakash
Abstract Palifermin has been demonstrated to decrease the incidence of severe oral mucositis in adults following TBI containing conditioning regimens prior to AHSCT. The impact of palifermin on the incidence of oral mucositis in children undergoing AHSCT has never been studied. We compared the effect of palifermin on the incidence of oral mucositis and supportive care in 58 children undergoing myeloablative AHSCT; 25 children received palifermin and 33 children did not receive palifermin (control arm). Oral mucositis was graded as per WHO criteria. The demographic characteristics were comparable between the two arms. Results comparing the palifermin vs. control arm showed that the incidence of grade III–IV oral mucositis was 20% vs. 42.4% (p = 0.072). The number of days patients received patient‐controlled analgesia and total parenteral nutrition in the palifermin vs. control arm were 8.80 ± 8.39 vs. 8.30 ± 8.54 (p = 0.826) and 13.52 ± 11.32 vs. 11.55 ± 9.63 (p = 0.484), respectively. The average length of hospitalization in the palifermin vs. control arm was 31.44 ± 7.42 vs. 28.61 ± 10.38 (p = 0.252), respectively. In this study, we were unable to demonstrate a statistical difference in the incidence of oral mucositis and other supportive care needs or a decrease in hospital stay between the two arms.